2015
DOI: 10.1371/journal.pone.0123885
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Benefits in Ant-Hemipteran Mutualism? The Case of the Ghost Ant Tapinoma melanocephalum (Hymenoptera: Formicidae) and the Invasive Mealybug Phenacoccus solenopsis (Hemiptera: Pseudococcidae)

Abstract: Although density-dependent benefits to hemipterans from ant tending have been measured many times, few studies have focused on integrated effects such as interactions between ant tending, natural enemy density, and hemipteran density. In this study, we tested whether the invasive mealybug Phenacoccus solenopsis is affected by tending by ghost ants (Tapinoma melanocephalum), the presence of parasitoids, mealybug density, parasitoid density and interactions among these factors. Our results showed that mealybug c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Although both the colony growth and parasitism of mealybugs decreased under extreme temperature (32 °C), ant tending level and aggression were greatly enhanced. It has been demonstrated that there is a positive linear relationship between ant tending level and mealybug colony growth rate 35 , which suggests that temperature warming could promote mealybug colony growth directly or indirectly. Thus, the net effect of temperature warming is to increase mealybug colony by benefiting ghost ant-mealybug mutualism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although both the colony growth and parasitism of mealybugs decreased under extreme temperature (32 °C), ant tending level and aggression were greatly enhanced. It has been demonstrated that there is a positive linear relationship between ant tending level and mealybug colony growth rate 35 , which suggests that temperature warming could promote mealybug colony growth directly or indirectly. Thus, the net effect of temperature warming is to increase mealybug colony by benefiting ghost ant-mealybug mutualism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ant foraging frequency mediates the tending level and protection ability for hemipterans 32 , 33 . Benefits to hemipterans are positively and linearly related to ant tending level 26 , 34 , 35 . Aphids directly respond to elevated temperature with decreased developmental time and reduced adult and progeny weight 36 , 37 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Those results may suggest that the ant tending level is mediated by host plants. It is clear that the intensity of mutualisms and the ant tending level can be affected by the temporal factor, age-specific, and the density of the hemipterans (Cushman & Whitham, 1989;Breton & Addicott, 1992;Itioka & Inoue, 1996;Morales, 2000;Zhou et al, 2015a). In contrast, few studies of ant-hemipteran mutualisms reported the patterns of host plants-dependent effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, mutualism is seemingly independent of the density of the animal species involved. One study showed that the benefit provided by T. melanocephalum to mealybugs was not significantly affected by the density of either mealybugs or the parasitoid A. bambawalei (Zhou et al 2015c).…”
Section: Mutualistic Relationship With Antsmentioning
confidence: 99%